2021
DOI: 10.1002/anie.202103990
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Oligosaccharide Antigens for Semi‐Synthetic Glycoconjugate Vaccine Leads against Streptococcus suis Serotypes 2, 3, 9 and 14**

Abstract: Streptococcus suis bacteria are one of the most serious health problems for pigs and an emerging zoonotic agent in humans working in the swine industry. S. suis bacteria express capsular polysaccharides (CPS) a major bacterial virulence factor that define the serotypes. Oligosaccharides resembling the CPS of S. suis serotypes 2, 3, 9, and 14 have been synthesized, glycans related to serotypes 2 and 9 were placed on glycan array surfaces to screen blood from infected pigs. Lead antigens for the development of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…The stereoselectivity is the result of the participating Lev ester in 2. [24] Similarly, the [1 + 2] glycosylation of disaccharide 20 with building block 3 catalyzed by NIS and TfOH yielded the trisaccharide 4 with complete β-selectivity. The cleavage of Lev esters was followed by the conversion of the hydroxyl groups in 21 into triflates using Tf 2 O and pyridine, concomitant replacement with tetrabutylammonium azide (TBAN 3 ) in the axial positions gave the desired azide 5 in 72 % yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stereoselectivity is the result of the participating Lev ester in 2. [24] Similarly, the [1 + 2] glycosylation of disaccharide 20 with building block 3 catalyzed by NIS and TfOH yielded the trisaccharide 4 with complete β-selectivity. The cleavage of Lev esters was followed by the conversion of the hydroxyl groups in 21 into triflates using Tf 2 O and pyridine, concomitant replacement with tetrabutylammonium azide (TBAN 3 ) in the axial positions gave the desired azide 5 in 72 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…Trisaccharide skeleton 4 can be obtained by [1 + 1] and [1 + 2] glycosylations, the β-selectivity could be ascertained by the neighboring participation of 2-OLev groups. [24] The total synthesis commenced with the preparation of the orthogonally protected rare sugar building blocks (Scheme 1). d-Bacillosamine derivative 1 was synthesized starting from the α-selective glycosylation of selenoglycoside 6 [25] with aminopropyl linker 7 using NIS/TMSOTf as a promoter to give α-linked glycoside 8 in 85 % yield.…”
Section: Resultsmentioning
confidence: 99%
“… Capsular polysaccharide repeating unit structures for Streptococcus suis serotypes 2, 14, 1/2 and 1 and 14 ( Van Calsteren et al, 2010 ; Van Calsteren et al, 2013 ; Van Calsteren et al, 2016 ), as well as the structure of three Ss2 oligosaccharide vaccine candidates, labelled frag3, frag4 and frag5 ( Zhang et al, 2021 ). The graphical representations use the Symbol Nomenclature for Glycans (SNFG) ( Varki et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, prior work demonstrated that the sialic acid moiety is not essential for CPS recognition by an Ss2-specific antibody ( Lecours et al, 2012 ). To further complicate matters, recent investigation of three oligosaccharide lead antigens for Ss2 (labelled frag3, frag4 and frag5 in Figure 1 ) showed efficacy for a penta- and a hexasaccharide (frag4 and frag5), but not the tetrasaccharide (frag3), indicating that sialic acid is not a necessary component of a minimal protective epitope for Ss2 ( Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such oligosaccharides possess a strictly defined chemical structure, do not contain bacterial contaminants, and can be conjugated with carrier proteins in a controlled fashion. Glycoconjugate vaccine candidates containing synthetic oligosaccharide ligands have been actively developed in past decades ( Gening et al, 2015 ; Kaplonek et al, 2018 ; Micoli et al, 2019 ; Gening et al, 2021 ; Javed and Mandal, 2021 ; Seeberger, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%